O fundo constitucional de financiamento do Nordeste e o desenvolvimento regional : o caso dos estados da Bahia e Pernambuco (1989-2010) - Santos, Wesley (2014)
This thesis aims to evaluate the impact of the Constitutional Fund for Financing the Northeast (FNE) in the state of Bahia and Pernambuco economies in the period 1989-2010. Objective accordingly verify the spatial and sectoral allocation of investment has contributed to a better geographical distribution of economic activity fulfilling their goals. Furthermore, analyzing their impact on the supply chain of these States, to establish whether the investments are distributed on a priority basis and estimate job creation based on RAIS data, checking the evolution of formal employment. For both our territorial clipping is based on a micro IBGE classification and our main database, in addition to sources already cited also includes management reports and data FNE kindly made available by the Ministry of National Integration (MI), in addition to data obtained from the publications of the Bank of Northeast Brazil (BNB). We conclude that although the FNE have considerable importance in the structuring of the northeastern economy and the states concerned, their actions were much more constrained by the logic of the market than by networking with a national regional development policy. However, there is an undeniable contribution to devolution of productive activities within the region, although this devolution is happening imperfectly and directed the few regions and even less complex sectors are the biggest beneficiaries. Finally, we conclude that the macroeconomic framework of the region and the states analyzed, although impacted by the FNE, still lacks a more fruitful role of the public sector on the articulation of a national development policy.